2007
DOI: 10.3938/jkps.51.1713
|View full text |Cite
|
Sign up to set email alerts
|

Growth of a One Dimensional Quasiperiodic Covering with Locally Determined Decorations

Abstract: A growth mechanism for a perfect one-dimensional (1D) quasiperiodic structure is presented with a local covering rule. We use rectangular tiles with two different types of string decorations. The string position in a tile is allowed to move when the tile is attached to an existing patch. By adjusting the position properly with local information, we show that a growth of perfect quasiperiodic structure is possible. This observation may provide new insight into how quasicrystals grow with perfect quasiperiodic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…As shown in Figure 2b, the capacitance ( C ox ) of the ZrO 2 dielectric can be extracted from the accumulation region, which indicates that the different ALD growth temperature results in the change of C ox . [ 27 ] For the ZrO 2 dielectric grown at 100, 150, 200, 250, and 280 °C, the extracted values of C ox are 0.599, 0.659,0.747, 0.849, and 0.941 μF cm −2 , respectively. It is observed that as the growth temperature increases, the value of the accumulated capacitance increases.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2b, the capacitance ( C ox ) of the ZrO 2 dielectric can be extracted from the accumulation region, which indicates that the different ALD growth temperature results in the change of C ox . [ 27 ] For the ZrO 2 dielectric grown at 100, 150, 200, 250, and 280 °C, the extracted values of C ox are 0.599, 0.659,0.747, 0.849, and 0.941 μF cm −2 , respectively. It is observed that as the growth temperature increases, the value of the accumulated capacitance increases.…”
Section: Resultsmentioning
confidence: 99%